2021
DOI: 10.1097/icu.0000000000000784
|View full text |Cite
|
Sign up to set email alerts
|

Systemic retinal biomarkers

Abstract: Purpose of review Systemic retinal biomarkers are biomarkers identified in the retina and related to evaluation and management of systemic disease. This review summarizes the background, categories and key findings from this body of research as well as potential applications to clinical care. Recent findingsPotential systemic retinal biomarkers for cardiovascular disease, kidney disease and neurodegenerative disease were identified using regression analysis as well as more sophisticated image processing techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Numerous studies have focused on the identification of systemic biomarkers (mostly for AD and PD) that can be obtained noninvasively, are sensitive and specific, and are reliable [2 ]. However, to our knowledge, most of these studies do not collect ocular imaging data despite the fact that AI-DLS has already shown its ability to identify a number of retinal systemic biomarkers or oculomics in large populations studies [7,74]. AI using ophthalmologic imaging parameters thus has a potentially important role in the diagnosis and monitoring of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have focused on the identification of systemic biomarkers (mostly for AD and PD) that can be obtained noninvasively, are sensitive and specific, and are reliable [2 ]. However, to our knowledge, most of these studies do not collect ocular imaging data despite the fact that AI-DLS has already shown its ability to identify a number of retinal systemic biomarkers or oculomics in large populations studies [7,74]. AI using ophthalmologic imaging parameters thus has a potentially important role in the diagnosis and monitoring of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review suggests that retinal photographs could be used in deep learning techniques for prediction of systemic diseases, including cardiovascular disease, while retinal optical coherence tomography (OCT) and optical coherence tomography angiography (OCT-A) are being used in prediction of cardiovascular disease in non-deep learning studies [37]. Considering the accessibility, non-invasive origin of retinal examination and its possible resemblance to coronary arteries we aimed to investigate the associations between ophthalmic parameters, CYP4F2 (rs2108622) and ABCA1 (rs1883025) polymorphisms and CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Oculomics, a rapidly developing field dedicated to identifying ocular biomarkers for systemic disease, is gaining attention for several cardiovascular and neurological applications [ 7 ]. A variety of retinal microvasculature features have become recognizable for their associations with systemic disease states [ 8 ]. Optical coherence tomography angiography (OCT-A) has emerged as a powerful clinical tool to image the retinal capillary bed, as it provides higher transverse and axial resolution than conventional color fundus photography or intravenous fluorescein angiography [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%